Introducing ecoprint batik at Rt 19 Dukuh Kembang: creativity inspired by nature - Prasestiyo, Hamudi; Hanifah, Halim Fathan Nurlaila; Pradana, Akhmad Danu Shafar; Alifia, Dita Nur; Palevi, Pramada Lian; Yuliano, Nandito Raka (Hasil Karya 'Aisyiyah untuk Indonesia, 2026)
The introduction of ecoprint batik techniques to children and adolescents in Dukuh Kembang represents an educational effort aimed at fostering creativity, ecological awareness, and local cultural preservation from an early age. Ecoprint utilizes natural materials such as leaves, flowers, and twigs as dyes and patterns on fabric, making it environmentally friendly and easy to implement with resources available in the local community. Participants were involved in all stages of the process, ranging from material collection and motif arrangement to dyeing and color fixation. The results demonstrated that participants were able to produce artistic works with aesthetic value and economic potential. This program also served as a means of optimizing local resources while strengthening the harmonious relationship between humans and nature. Furthermore, it provides a foundation for building ecological awareness and creative economic empowerment among the village’s younger generation.